Cultural-Back Translation in Video Games: A Case Study of Cultural Specific Elements in A Space for the Unbound - Medina, Rania Alya; Wijaya, Andika (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2026)
Video games, as a rapidly expanding industry, have increasingly become a subject of translation studies, particularly as more titles are localized into multiple languages to reach global audiences. This paper examines the cultural-back translation of culture-specific elements in the Indonesian-produced video game A Space for the Unbound (2023), whose narrative was originally written in English and later translated into Indonesian. The study identifies culture-specific elements using Newmark’s (1998) categorization and analyzes the translation procedures applied based on Shirinzadeh and Mahadi (2014), from which the underlying translation ideology is inferred following Venuti (2017). The findings reveal that, out of 157 identified culture-specific elements, 52% were translated using procedures aligned with domestication. This indicates that the developers, particularly the narrative writers and the localization team, aimed to accommodate Indonesian players while preserving a balanced experience for English-speaking audiences. The study contributes to video game translation research by highlighting cultural-back translation practices and suggests that future research may examine inconsistent multilingual in-game assets as well as translations into other supported languages.